2011
DOI: 10.1007/s10637-011-9750-1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental antiangiogenic agents for the treatment of Non-Small Cell Lung Cancer (NSCLC)

Abstract: Standard therapy for advanced or metastatic non-small cell lung cancer (NSCLC) has primarily consisted of traditional cytotoxic chemotherapy, although use of targeted therapies has been approved in specific settings. Antiangiogenic agents represent a promising therapeutic strategy for treatment of advanced NSCLC. Bevacizumab is currently approved when given in combination with first-line platinum-based therapy in selected patients with nonsquamous NSCLC. Bevacizumab may also provide benefit in other clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Traditional surgery, radiotherapy, and chemotherapy are still the only treatment options for most advanced NSCLC patients, but these treatments are unsatisfactory (Choi et al, 2010). Consequently, more and more studies have begun to investigate lung cancer from the perspective of the TME, especially inflammation; actively explore targets related to anti-angiogenesis, immune regulation, and EMT in the microenvironment; and develop more therapeutic targets (Blumenschein, 2012). For example, Logsdon et al found that in the presence of carcinogenic Ras, inflammatory stimulation initiates a positive feedback loop involving NF-κB, which further amplifies the activity of Ras to the pathological level (Figure 6).…”
Section: Progress In the Treatment Of Lung Cancer Based On Inflammation And Inflammatory Microenvironmentmentioning
confidence: 99%
“…Traditional surgery, radiotherapy, and chemotherapy are still the only treatment options for most advanced NSCLC patients, but these treatments are unsatisfactory (Choi et al, 2010). Consequently, more and more studies have begun to investigate lung cancer from the perspective of the TME, especially inflammation; actively explore targets related to anti-angiogenesis, immune regulation, and EMT in the microenvironment; and develop more therapeutic targets (Blumenschein, 2012). For example, Logsdon et al found that in the presence of carcinogenic Ras, inflammatory stimulation initiates a positive feedback loop involving NF-κB, which further amplifies the activity of Ras to the pathological level (Figure 6).…”
Section: Progress In the Treatment Of Lung Cancer Based On Inflammation And Inflammatory Microenvironmentmentioning
confidence: 99%
“…The important role of angiogenesis in tumor development, growth, and metastasis is well established [1] . Angiogenesis inhibitors, including the anti−vascular endothelial growth factor (VEGF) monoclonal antibody bevacizumab; the recombinant anti-VEGF fusion protein aflibercept; and the receptor tyrosine kinase inhibitors sorafenib, sunitinib, axitinib, vandetanib, and pazopanib, have been shown to improve outcomes for patients with certain cancer types, either as monotherapy or combined with chemotherapy [2] [4] . However, only a fraction of treated patients typically derive clinical benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Supportive therapy, surgery, and RT remain the mainstays of management for these patients. Additional areas of active research include techniques to preserve neurocognitive functions with radiotherapy (20, 52), improving the detection and clinical utility of circulating tumor cells (53), and novel systemic approaches including immunotherapy alone (54, 55) or in combination with radiotherapy (56), anti-metabolic agents (57), anti-angiogenesis drugs (58), and novel targeted therapies for a growing list of oncogenic mutations (59). Ultimately, the optimal management strategy will employ a multi-disciplinary approach accounting for individual characteristics of both patient and tumor.…”
Section: Resultsmentioning
confidence: 99%